Manufacturing and evaluation of Large-scale Composite Bumper System for bridge pier protection against ship collision. (15th December 2016) - Fang, Hai; Mao, Yifeng; Liu, Weiqing; Zhu, Lu; Zhang, Bing
Abstract: An innovative Large-scale Composite Bumper System (LCBS) for bridge piers against ship collision was recently proposed at Nanjing Tech University. The modular segment of LCBS is made of Glass Fiber-Reinforced Polymer (GFRP) skins, GFRP lattice webs, Polyurethane (PU) foam cores and ceramic particles in which Vacuum Assisted Resin Infusion Process (VARIP) is adopted in the manufacturing process. This novel bumper system offers several remarkable advantages, such as: self-buoyancy in water, modular fabrication of segments, efficiency for on-site installation, excellent corrosion resistance, as well as ease in replacing damaged segments. In this paper, the manufacture procedures as well as the installation process of LCBS were introduced. An in-depth analysis of performance evaluation of LCBS was then conducted for a real cable stayed bridge using a nonlinear explicit dynamic finite-element analysis program (LS-DYNA). The simulation results indicated that LCBS can effectively increase the impact time of ship-bridge collision, and reduce the peak collision forces to a non-destructive level, leading to a good effect in energy dissipation. The results suggest that LCBS is an effective bumper system for protecting bridges and ships in ship-bridge collisions.